2022
DOI: 10.1136/rmdopen-2021-001652
|View full text |Cite|
|
Sign up to set email alerts
|

Need and value of targeted immunosuppressive therapy in giant cell arteritis

Abstract: Despite the heterogeneity of the giant cell arteritis (GCA) at the level of clinical manifestations and the cellular and molecular players involved in its pathogenesis, GCA is still treated with standardised regimens largely based on glucocorticoids (GC). Long-term use of high dosages of GC as required in GCA are associated with many clinically relevant side effects. In the recent years, the interleukin-6 receptor blocker tocilizumab has become available as the only registered targeted immunosuppressive agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It has been shown that Th1 cells may persist during treatment with glucocorticoids [ 28 ]. There is a great variety of potential future target therapies currently in clinical trials; the demonstration of such a Th1 cell signal may have implications for the use of targeted therapy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Th1 cells may persist during treatment with glucocorticoids [ 28 ]. There is a great variety of potential future target therapies currently in clinical trials; the demonstration of such a Th1 cell signal may have implications for the use of targeted therapy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several targeted immunosuppressive drugs have been used as add-on to GCs, with the aim of reducing long term GC use and related toxicity ( 130 ). As expected based on the biology of IL-6, and its role in GCA, IL-6 inhibition by the anti-IL-6 receptor antibody tocilizumab is effective in GCA that has been verified by biopsy or large vessel imaging, and enables rapid GC tapering with reduced risk of relapse ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is used to treat psoriatic arthritis, generalized pustular psoriasis, and erythrodermic psoriasis. it is an ongoing clinical trial, NCT04633447, that aims to evaluate, as its primary purpose, the efficacy of guselkumab compared to placebo, in combination with a 26-week GC taper regimen, in adult participants with new-onset or relapsing GCA [7]…”
Section: Non-glucocorticoid Immunomodulatory Medications: Monoclonal ...mentioning
confidence: 99%
“…It is used to treat psoriatic arthritis, generalized pustular psoriasis, and erythrodermic psoriasis. it is an ongoing clinical trial, NCT04633447, that aims to evaluate, as its primary purpose, the efficacy of guselkumab compared to placebo, in combination with a 26-week GC taper regimen, in adult participants with new-onset or relapsing GCA [7] Secukinumab Secukinumab, a fully human mAb that selectively inhibits IL-17A, was studied in phase two randomized controlled trial of 52 patients with new-onset or exacerbation GCA who were biologic-na€ ıve. Patients were randomized into two arms, one treated with secukinumab 300 mg, the other with a placebo administered weekly for 5 doses and then every 4 weeks until week 48, combined with a taper of prednisolone at 26 weeks.…”
Section: Guselkumabmentioning
confidence: 99%